Analysis of Systemic Risk in the Chinese Insurance Market Based on Reinsurance Networks - Wei, Wang; Ming, Liu (Advances in Social Sciences Research Journal, 2023)
Since the financial crisis in 2008, regulators around the world have been committed to understanding and mitigating the potential systemic risks brought by the insurance industry, focusing on the risk transmission field within the insurance industry. This paper focuses on the possible transmission relationship of systemic risk in China’s insurance market through the reinsurance network from the perspective of macro-prudential, discusses the accumulation and contagion effect of systemic risk over time, and puts forward suggestions on the macro-prudential supervision of China’s insurance industry.